Sexually transmitted infections amongst men who have sex with men (MSM) in South Africa. - Rujeko Mashingaidze; Zoe Moodie; Mary Allen; Linda-Gail Bekker; Doug Grove; Nicole Grunenberg; Yunda Huang; Holly E Janes; Erica Maxine Lazarus; Mookho Malahleha; Maphoshane Nchabeleng; Fatima Laher (Public Library of Science (PLoS), 2023)
There is limited data about bacterial STIs in MSM populations in sub-Saharan Africa. Our retrospective analysis used data from the HVTN 702 HIV vaccine clinical trial (October 2016 to July 2021). We evaluated multiple variables. Polymerase chain reaction testing was conducted on urine and rectal samples to detect Neisseria gonorrhoea (NG) and Chlamydia trachomatis (CT) every 6 months. Syphilis serology was conducted at month 0 and thereafter every 12 months. We calculated STI prevalence and the associated 95% confidence intervals until 24 months of follow-up. The trial enrolled 183 participants who identified as male or transgender female, and of homosexual or bisexual orientation. Of these, 173 had STI testing done at month 0, median age was 23 (IQR 20-25) years, with median 20.5 (IQR 17.5-24.8) months follow-up (FU). The clinical trial also enrolled and performed month 0 STI testing on 3389 female participants, median age 23 (IQR 21-27) years, median 24.8 (IQR 18.8-24.8) months FU and 1080 non-MSM males with a median age of 27 (IQR 24-31) years, median 24.8 (IQR 23-24.8) months FU. At month 0, CT prevalence was similar in MSM and females (26.0% vs 23.0%, p = 0.492) but was more prevalent in MSM compared to non-MSM males (26.0% vs 14.3%, p = 0.001). CT was the most prevalent STI among MSM at months 0 and 6 but declined from month 0 to month 6 (26.0% vs 17.1%, p = 0.023). In contrast, NG did not decline in MSM between months 0 and 6 (8.1% vs 7.1%, p = 0.680) nor did syphilis prevalence between months 0 and 12 (5.2% vs 3.8%, p = 0.588). Bacterial STI burden is higher in MSM compared to non-MSM males, and CT is the most prevalent bacterial STI amongst MSM. Preventive STI vaccines, especially against CT, may be helpful to develop.